Recursive construction of hierarchical Fibonacci Cubes and hierarchical extended Fibonacci Cubes - Karci, A (Ieee Computer Soc, 2001)
The hierarchical Fibonacci cubes and hierarchial extended Fibonacci cubes are recursively constructed in this paper. This property comes from the point of these derived networks. These nets are basically derived from Fibonacci series, which is recursive series.
8th International Conference on Parallel and Distributed Systems (ICPADS 2001) -- JUN 26-29, 2001 -- KYONGJU CITY, SOUTH KOREA
Keywords: hierarchical interconnection networks; Fibonacci Cubes; extended Fibonacci Cubes; interconnection networks; hierarchical Fibonacci Cubes; hierarchical extended Fibonacci Cubes.